(untitled) (Revista de Ciências Agroveterinárias, 2006)
The soil physical quality has been extensively studied so that appropriate parameters can be established for its assessment. The relative bulk density (DR), which is the ratio between the filed observed value (DS) and the laboratory determined maximum density (DMS), has been an alternative to assess soil quality. Samples of an Oxisol were collected and the maximum density was determined in laboratory, using the standard Proctor test. The bulk density where water maximum availability to plants occurs with minimal restriction to root growth was also assessed. The ideal density for the analyzed soil was 1.08 Mg m-3, whereas the DMS was 1.51 Mg m-3. These results indicate that the Oxisol DR for optimum and limiting plant growth conditions are 0.71 and C 0.88, respectively.